personalAnthropology by Lersch and environments of consciousness within the framework of hermeneutics of the Self by G. W. Allport - Maurial Chávez, Iván (2021)
This article, by means of the categories of philosophical hermeneutics, explains how it is possible to approach the way in which the thematic of transitivity and the individual Self develops according to the Philipp Lersch’s phenomenological anthropology. Interpretation work is carried out through exploration of the development of the Self, described by Gordon W. Allport. In this regard, methodology used can serve as a methodological setting for hermeneutics of personality where it is feasible to recognize the behavior of the dual imperatives of consciousness. This hermeneutic of personality will lay the foundations for a theoretical exploration of how consciousness has been shaped as a vital impulse which has bifurcated, being the individual the moment of encounter of such bifurcation in the form of bio-culture.